Women's Success in Academic Science: Challenges to Breaking Through the Ivory Ceiling. Issue 8 (August 2015) - Henley, Megan M.
Abstract Although a greater number of women are entering academic science than ever before, women remain underrepresented and are perceived as less successful than men in their fields. The reasons behind this are complicated and debatable. In this paper, I review the challenges that women continue to face in the natural and social academic sciences. Women continue to face barriers toward obtaining academic positions and securing promotions. A crucial aspect of the problem lies in the subjective definition of "success, " which creates subconscious biases as well as gendered processes within institutions. These processes include biased evaluations of success in academia, limited mentorship for women in science, limited networking opportunities, and lack of institutional support for mothers. Future research should look more closely at the gendered definition of success, and related constraints within academia that keep women from breaking through the ivory ceiling.